A framework for resource maintenance and enhancement - Audouin, Michelle Ann (Department of Environmental and Geographical Science, 2024)
Our understanding of how to integrate the goals of development and those of the environment, is our map or instruction manual on practically addressing the current global environmental crisis. Our knowledge provides us with the means by which we can "do things in the world or cope with events (Sayer, 1992:59)." In this dissertation, increasing this understanding is not only the guide to the development of a framework for resource maintenance and enhancement, but also the means by which we maintain and enhance resources. To establish 'a map' for integrating environmental and developmental goals the concept of sustainable development, with its strategies for various resource sectors, was expanded and explained in the Brundtland Report (World Commission on Environment and Development (WCED), 1987). The Report defined sustainable development as aiming "to meet the needs of present generations, without compromising the ability of future generations to meet their own needs (Lebel and Kane, 1987)." It includes two components: the concept of needs, especially those of the world's poor; and the idea of limitations that are imposed by technology and society on the environment to meet those needs (Lebel and Kane, 1987).